2022
DOI: 10.1016/j.chest.2021.07.2170
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Ozone Effects on Human Lung Function, 2013 Through 2020

Abstract: BACKGROUND: Ozone effects on lung function are particularly important to understand in the context of the air pollution-health outcomes epidemiologic literature, given the complex relationships between ozone and other air pollutants with known lung function effects.RESEARCH QUESTION: What has been learned about the association between ozone exposures and lung function from epidemiology studies published from 2013 through 2020?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 55 publications
1
32
0
1
Order By: Relevance
“…The range of magnitude in the association we found between short-term O 3 and evening FEV 1 is comparable to previous studies, with a lower limit of −5.2% expected reduction in %predicted FEV 1 (−2.65 [−5.19, −0.10]). For example, a previous literature review reported that short-term O 3 exposure was associated with a wide range of reduction in %predicted FEV 1 in children (−0.01% to −9% reduction per 10 ppb change in O 3 ), for periods ranging from 1 day to 2 weeks [ 37 ]. Similarly, expected changes as large as −9.3% reduction in morning %predicted FEV 1 and −9.3% reduction in morning %predicted PEF were seen with lag 1 traffic-related NO x exposure (lower 95% CI limit, Supplementary Tables S4 and S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The range of magnitude in the association we found between short-term O 3 and evening FEV 1 is comparable to previous studies, with a lower limit of −5.2% expected reduction in %predicted FEV 1 (−2.65 [−5.19, −0.10]). For example, a previous literature review reported that short-term O 3 exposure was associated with a wide range of reduction in %predicted FEV 1 in children (−0.01% to −9% reduction per 10 ppb change in O 3 ), for periods ranging from 1 day to 2 weeks [ 37 ]. Similarly, expected changes as large as −9.3% reduction in morning %predicted FEV 1 and −9.3% reduction in morning %predicted PEF were seen with lag 1 traffic-related NO x exposure (lower 95% CI limit, Supplementary Tables S4 and S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, VOCs can undergo photochemical reactions with nitrogen oxides (NO x ) and ultraviolet (UV) radiation to produce ground-level O 3 [7]. Exposure to groundlevel O 3 has been associated with decreased lung function [8] and pre-term births [9]. Secondly, VOCs emitted from biogenic and anthropogenic sources can react to form secondary organic aerosols (SOAs) [10,11], which contribute to PM 2.5 and smog [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Ozone is perhaps the best studied air pollutant in terms of acute respiratory effects, and review of recent evidence confirms that short-term exposure is associated with acute decrements in lung function ( 1 ). In fact, the National Ambient Air Quality Standard for ozone promulgated by the U.S. Environmental Protection Agency is based primarily on evidence from multiple controlled human-exposure studies conducted over the past several decades showing acute decrements in lung function ( 2 ).…”
mentioning
confidence: 99%
“…In fact, the National Ambient Air Quality Standard for ozone promulgated by the U.S. Environmental Protection Agency is based primarily on evidence from multiple controlled human-exposure studies conducted over the past several decades showing acute decrements in lung function ( 2 ). Multihour ozone concentrations of 80 ppb or higher consistently produce significant decreases in FEV 1 and FVC in healthy adults that typically resolve within 24 hours ( 1 , 2 ). Multiple epidemiological studies have also demonstrated acute decrements in spirometric lung function with real-world exposures during exercise ( 1 4 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation